Native mitral valve staphylococcus endocarditis with a very unusual complication: Ruptured posterior mitral valve leaflet aneurysm. Issue 1 (18th December 2021) - Maidman, Samuel D.; Kiefer, Nicholas J.; Bernard, Samuel; Freedberg, Robin S.; Rosenzweig, Barry P.; Bamira, Daniel; Vainrib, Alan F.; Ro, Richard; Neuburger, Peter J.; Basu, Atreyee; Moreira, Andre L.; Latson, Larry A.; et al.
Abstract: Infective endocarditis (IE) is a life‐threatening disease associated with in‐hospital mortality of nearly one in five cases. IE can destroy valvular tissue, which may rarely progress to aneurysm formation, most commonly at the anterior leaflet in instances of mitral valve involvement. We present a remarkable case of a patient with IE and a rare complication of a ruptured aneurysm of the posterior leaflet of the mitral valve. Two‐ and Three‐dimensional transesophageal echocardiography, intra‐operative videography, and histopathologic analysis revealed disruption at this unusual location–at the junction of the P2 and P3 scallops, surrounded by an annular abscess.